The Use and Misuse of Positivism in Economics - Lama, Sunny (GS WOW: Wisdom of Worthy Research Journal, 2024)
This essay attempts to demonstrate controversies concerning positivism in the discipline of economics and reasons that have yet kept it alive. It suggests strategy that can simultaneously reduce the mechanical methodological aspect and increase the predictive power of positivist approaches. The paper employs a critical theoretical approach, wherein the inadequacy of positivism is discussed with relations to economic theories. The findings suggest that the nature of social science itself does not let any methodology hold its ground firmly. The combined application of “common rationality”and “social rationality” can simultaneously reduce the mechanical methodological aspect and increase the predictive power of positivist approaches. Drawing on the criticisms leveled upon positive economics, a novel model is envisioned for more reliable economic theory-making, which involves the fusion of  “common rationality” and “social rationality”.